Cognitive, Emotional, and Behavioral Disorders in Children with Respiratory Allergic Diseases: Causes and Solutions - Natalia V. Ustinova; George A. Karkashadze; Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2024)
The publication is devoted to the review of accumulated data on the relationship of respiratory allergopathology with neuropsychiatric disorders in childhood. The immediacy of the problem is due to the mutual influence of allergic and neuropsychiatric conditions combined in a child on the course of these diseases. According to research, the connection of respiratory allergic diseases with disorders of neurodevelopment, in particular with attention deficit and hyperactivity disorder and autism spectrum disorders, is clearly manifested, and the first publications on the connection with speech and other mild cognitive impairments have appeared. At the same time, the formation of depression, suicidal behavior, and anxiety disorders in respiratory allergopathology is being actively studied. It is assumed that the close relationship between nervous and immune regulation provides a high correlation of allergic and neuropsychiatric pathological conditions, although cause-and-effect relationships have not yet been precisely established. In this regard, it becomes relevant to introduce into clinical practice monitoring of cognitive status, neuropsychic development and possible symptoms of anxiety, depression and suicidal thoughts in the treatment of children with respiratory allergic diseases. Timely detection of violations will make it possible to provide specialized interventions at an early stage in order to achieve a favorable treatment result in the long term.